Non-collaborative Telepresentations Come of Age - Gemmell, Jim; Bell, Gordon (Association for Computing Machinery, Inc., 1997)
A Telepresentation is a presentation in which the presenter and/or some of the audience members are not physically present but are telepresent – in a different location and/or at a different time. Telepresentations promise to reach a wider audience by transmitting and/or recording the presentation for viewing at a different place and/or time and time-scale. The result dramatically reduces travel costs, increases communication, and provides a meeting record. Today, telepresentations are being used for training, product introductions, and general information meetings. We believe telepresentations will soon find regular use for courses and conferences. It is now possible for anyone, anywhere to produce a telepresentation at low cost, on PCs, using today’s internet/intranet and telephony infrastructure. We call for all technical conferences to be telepresent. Telepresentations may just be the next "killer app".